2013
DOI: 10.1111/tid.12164
|View full text |Cite
|
Sign up to set email alerts
|

Currently recommended BK virus (BKV) plasma viral load cutoff of ≥4 log10/mL underestimates the diagnosis of BKV‐associated nephropathy: a single transplant center experience

Abstract: Utilizing the current AST guideline cutoff of ≥4 log10 /mL, the PCR Assay A underestimated the diagnosis of BKVAN. Urgent standardization of the various BKVL assays and establishment of universal cutoff points is imperative to avoid BKVAN-related graft loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
43
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 17 publications
1
43
0
4
Order By: Relevance
“…The wide variety of in-house quantitative real-time PCR assays and the lack of international standards result in an important interlaboratory disagreement with respect to BKVL measurements (12) and thus far have hindered the establishment of a universal BKVL cutoff value with a high positive predictive value for presumptive BKVN (13,14). Commercially available quantitative PCR kits are believed to provide more repeatable and reproducible results, consequently contributing to the efforts of clinical laboratories regarding the currently ongoing accreditation process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wide variety of in-house quantitative real-time PCR assays and the lack of international standards result in an important interlaboratory disagreement with respect to BKVL measurements (12) and thus far have hindered the establishment of a universal BKVL cutoff value with a high positive predictive value for presumptive BKVN (13,14). Commercially available quantitative PCR kits are believed to provide more repeatable and reproducible results, consequently contributing to the efforts of clinical laboratories regarding the currently ongoing accreditation process.…”
Section: Discussionmentioning
confidence: 99%
“…However, most BKV quantitative PCR methods are in-house techniques, and marked variability among assays has been described (12). A recent study demonstrated that, depending on the PCR assay, the currently recommended BKV viremia cutoff of Ն4 log 10 copies/ml may underestimate the prevalence of BKVN (13). The variability of the assays may be attributable to various criteria: features of primers and probe design, including the size of the amplicon and the choice of reference material and/or types of matrices used for the blood compartment (plasma or whole blood [WB]) (12,14).…”
mentioning
confidence: 99%
“…While BKV NAAT is integral to the management of BKV in transplantation, quantification variability between assays has prevented comparisons of BKV viral load results across institutions, making result interpretation challenging and variable. Though current guidelines recommend a plasma viral load of Ն10,000 copies/ml as the threshold for clinical intervention in kidney transplantation based on a specificity of 93% for BKVN, some centers have reported that this threshold may underestimate the diagnosis of BKVN and suggest using lower viral load thresholds (1,5,15). In fact, such discrepancies may be appropriate realities for institutions using different assays that produce different quantitative results for a given sample.…”
Section: Discussionmentioning
confidence: 99%
“…This variation can be due to the appropriateness of various diagnostic tests used for the detection of these viral infections. The threshold values used for diagnosis can also be a potential source of variation (10). One study in Korea showed that 10 (5.2%) out of 191 patients with renal transplant had BK virus associated nephropathy.…”
Section: Discussionmentioning
confidence: 99%